The Modern Physics Teaching based on the Interstellar film: A didactic approach to meaningful learning (Research, Society and Development, 2019)
The teaching of Physics has over the years gone through various challenges and difficulties. In order to improve teaching and learning of students, we have tried to generate new approaches that promote meaningful learning. Due to countless factors, the teaching of Modern Physics in high schools has been left in the background, causing students not to experience this fundamental area of Physics. This article aims to contribute to the teaching of Modern Physics in state schools in the city of Bragança-PA, seeking to show students the fundamental concepts of Modern Physics in a simple and contextualized way with the support of the Interstellar film. The work was carried out in the periods of April to December of 2017, in the Rio Caeté state school, being divided in three stages: Stage I, constituted of a diagnostic evaluation and classes of Modern Physics; Step II, Interstellar Film and Conceptual Evaluation; Step III; Modern physics classes with a new look, final assessment and opinion polls. The project raises pertinent discussions regarding the use of diagnostic evaluation, the use of films in Physics teaching and shows the students' feelings regarding teaching and learning of Physics, showing in their results a considerable sampling of meaningful learning and evidencing that it is necessary to create new ways of transmitting knowledge for meaningful learning